2009
DOI: 10.1111/j.1467-6494.2009.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Development of Harmonious and Obsessive Passion: The Role of Autonomy Support, Activity Specialization, and Identification With the Activity

Abstract: Recent research (Vallerand et al., 2003) has supported the existence of two types of passion for activities: a harmonious and an obsessive passion. The purpose of this investigation was to study the processes likely to lead to the development of passion. Three studies using correlational and short-term longitudinal designs with varied populations ranging from beginners to experts reveal that identification with the activity, activity specialization, parents' activity valuation, and autonomy support predict the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
363
3
33

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 370 publications
(426 citation statements)
references
References 55 publications
27
363
3
33
Order By: Relevance
“…The result are in line with the report from [7]- [14], [21]- [24], [28]- [30] that 1) social support and work resilience have direct effect on work passion, and 2) social support has indirect effect on work passion through work resilience. In contrast, the job characteristic variable has no significant effect on work passion of Thai Teachers in Municipal Schools.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The result are in line with the report from [7]- [14], [21]- [24], [28]- [30] that 1) social support and work resilience have direct effect on work passion, and 2) social support has indirect effect on work passion through work resilience. In contrast, the job characteristic variable has no significant effect on work passion of Thai Teachers in Municipal Schools.…”
Section: Discussionsupporting
confidence: 82%
“…A survey of employee passion found that social support (such as sharing experiences, supporting colleagues, free counseling) help pass on the passion, increased number of volunteers, higher participation rate, fosters their personal and professional development [20]. In addition, other research found that support helps create passion in the workplace [21]- [23]. Code of Conduct in The Teachers Council of Thailand's Regulation stated that the teacher must act in accordance with morals and ethics of profession in The Code of Conduct which including five area as follows: to oneself, to profession, to client, to co-professions, and to community.…”
Section: Introductionmentioning
confidence: 99%
“…Building on the conceptualization that obsessive passion is an inclination that originates from a controlled/pressured internalization (individuals rely heavily on the activity in question for own self-definition [Mageau, Vallerand, Charest, Salvy, Lacaille, Bouffard, & Koestner, 2009]), prior research has suggested that it becomes important to carefully design the valuation system: positive feedback should be unexpected rather than expected . By not anticipating positive feedback, the person can more easily separate his or her own identity and self-worth from activity achievements.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…À contrario, la passion obsessive exerce une pression, est contrôlante et laisse peu de place aux autres activités de la personne qui perd le contrôle de ses comportements, mais désire toujours nourrir sa passion (Vallerand, 2015). Depuis les années 1990, plus d'une centaine d'études auprès de populations d'âges et de continents variés ont porté sur la passion (Marsh et al, 2013) pour des activités variées telles que la musique (Mageau et al, 2009), l'enseignement (Carbonneau, Vallerand, Fernet et Guay, 2008), le sport (Vallerand, Losier et Pelletier, 2006) ou encore les jeux de hasard et d'argent (JHA) (Rousseau, Vallerand, Ratelle, Mageau et Provencher, 2002).…”
Section: Introductionunclassified